Food properties of quinoa and its paradoxes exclusion and social inclusion in Peru (2011-2014) - Ramírez Miranda, Durga (2017)
The central objective of the research is to determine the nutritional properties of quinoa and paradoxes of social exclusion and inclu-sion in Peru (2011-2014) .The method is used for analysis and synthesis. It has been applied in depth interviews with producers, and surveys of a sample of 100 people who were selected using non-probability sampling. They have identified the nutritional properties of quinoa compared with other foods and the positive impact of an economic nature that generates its growth, supply and demand in the market. S and explains the paradox of inclusion and exclusion of quinoa between those who produce, sell and consume quinoa and the reasons why producers do not consume the one hand not knowing the high nutritional value of the product and market it elsewhere prefer because it is the only economic resource of this town, located in the high Andean zones, which are still excluded from state support. Development policies of the cultivation and consumption of quinoa to be applied in Peru is exposed.